Food wars! : shokugeki no soma. 28 - Tsukuda, Yuto, 1989- (Shonen Jump advanced., 2019)
"In the third bout of the team shokugeki, Eizan designs his recipe specifically to negate the best qualities of Takumi's, but Takumi's expression remains confident as he pulls his creation from the oven. Just what secret weapon could Takumi's Italian dish hold? Meanwhile, both Soma and Megumi continue working their hardest in order to bring victory to the resisters as this bout reaches its thunderous conclusion!"--Back cover.